Discricionariedade judicial e hermenêutica pós-positivista - Parreira, Liziane (2013)
The present dissertation intends to examine the judicial discretion in order to check the limits of interpretation, under the approach of post-positivism. The study covers the main transformations of legal hermeneutics to analyze the new role which the interpreter has acquired in contemporary society. For both proposed to investigate the administrative discretion in the search for a concept most integral of judicial discretion and also the limits for a possible interpretation unmeasured. At the first part of the work are considered the main hermeneutical schools to understand how each author conceptualized the discretion within his theory. Next is presented administrative discretion and the limits as parameters for judicial discretion. At the third and the last part, we returned to the central thematic about the theories of authors like Ronald Dworkin to justify the necessity to adopt some criteria for interpretation. The purpose of this dissertation is to arrive a conclusion as to whether it is possible that judgments are based on solid instruments different of the normative and in what way the post-positivism contributes to give the interpreter greater freedom to build the individual standard.